Growth and proline content of potato Solanum tuberosum L. in vitro candidate tolerant to drought of origin callus - Bilter A. Sirait; Iovie P. Roselyna; . Charloq (Syiah Kuala University, 2013)
Screening of candidate tolerant potato (Solanum tuberosum L.) to drought in vitro from callus was aimed to determine the growth and proline content of potato plants. This research was conducted at the Laboratory of Tissue Culture of Dinas Pertanian of North Sumatra Province, Jl Karya Jasa No 6 Gedung Johor Medan, in May 2012 until May 2013. The initial research was callus formation followed byorganogenesis. Then, was treated by PEG, 1000, 2000 and 3000 ppm. The result indicated that increased concentration of PEG decreased the amount of leaves and number of internodes. The higher the PEG concentration, the higher the proline content of potato in vitro.